please help me solve Q.13
Attachments:
![](https://hi-static.z-dn.net/files/de7/57deb5b7487687cdb64aa6512b362577.jpg)
Answers
Answered by
1
Step-by-step explanation:
answer Bhai Log ----/////////////////////////
Attachments:
![](https://hi-static.z-dn.net/files/d36/1be322165fc11671377d44a171098764.jpg)
![](https://hi-static.z-dn.net/files/d6f/6d26f90584228f5bb1c8015351479ce6.jpg)
Answered by
3
Step-by-step explanation:
x + y + z = 0 ( given)
x^3 + y^3 + z^3 = 3 xyz
identity : x^3 + y^3 + z^3 - 3xyz = ( x+y+z) ( x^2 + y^2 + z^2 - xy - yz - zx)
LHS
x^3 + y^3 + z^3 - 3xyz
RHS
( x+y+z) ( x^2 + y^2 + z^2 - xy - yz - zx)
value of (x+y+z) is equal to 0
0 × ( x^2 + y^2 + z^2 - xy - yz - zx)
= 0
therefore
x^3 + y^3 + z^3 - 3xyz = 0
x^3 + y^3 + z^3 = 0 + 3xyz
x^3 + y^3 + z^3 = 3xyz
HOPE IT HELPS
Similar questions
History,
2 months ago
Computer Science,
2 months ago
Geography,
2 months ago
Biology,
4 months ago
Math,
11 months ago